Circadian Rhythmicity of Active GSK3 Isoforms Modulates Molecular Clock Gene Rhythms in the Suprachiasmatic Nucleus - Besing, R.C. (J Biol Rhythms, 2015)
The suprachiasmatic nucleus (SCN) drives and synchronizes daily rhythms at the cellular level via transcriptional-translational feedback loops comprised of clock genes such as Bmal1 and Period (Per). Glycogen synthase kinase 3 (GSK3), a serine/threonine kinase, phosphorylates at least five core clock proteins and shows diurnal variation in phosphorylation state (inactivation) of the GSK3β isoform. Whether phosphorylation of the other primary isoform (GSK3α) varies across the subjective day-night cycle is unknown. The purpose of this study was to determine if the endogenous rhythm of GSK3 (α and β) phosphorylation is critical for rhythmic BMAL1 expression and normal amplitude and periodicity of the molecular clock in the SCN. Significant circadian rhythmicity of phosphorylated GSK3 (α and β) was observed in the SCN from wild-type mice housed in constant darkness for two weeks. Importantly, chronic activation of both GSK3 isoforms impaired rhythmicity of the GSK3 target BMAL1. Furthermore, chronic pharmacological inhibition of GSK3 with 20 μM CHIR-99021 enhanced the amplitude and shortened the period of PER2::luciferase rhythms in organotypic SCN slice cultures. These results support the model that GSK3 activity status is regulated by the circadian clock and that GSK3 feeds back to regulate the molecular clock amplitude in the SCN.